Action-specific effects on perception are grounded in affordance perception: An examination of soccer players` action choices in a free-kick task - Paterson, G.; van der Kamp, J.; Bressan, E.; Savelsbergh, G. (Academia.edu, 2017)
The aim of the current study was to investigate how performance accuracy on a soccer free-kick task affects perception of the distance between the ball and goal and the perception of kickability. It was hypothesized that action-specific biases in perception of environmental properties (i.e., distance) would be grounded in affordance perception (i.e., kickability). We used a modified staircase procedure in order to investigate the accuracy with which skilled soccer players were able to perceive whether free-kick situations presented over a wide range of distances from goal were kickable or not. Participants were also required to estimate the distances of the free-kicks from goal using a perceptual-matching task. Results showed that distance perception was correlated with kicking performance, but only at the boundary of the participants` perceived kickability. It was also found that perception of kickability was more strongly related to success in the free-kick task than distance perception per se. Results support the notion derived from Proffitt's (2006) account that action-specific effects on the perception of the environment properties are grounded in the perception of affordances.